Determination of Pyrethroid Pesticides in Vegetables by Solid-Phase Extraction Cleanup and Gas Chromatography - Chai, Alvin Lian Kuet; Lau, Seng (Universiti Putra Malaysia Press, 2003)
A simple and rapid method has been developed for the simultaneous determination of five pyrethroid pesticides in vegetables. Residues were extracted with acetone and methylene chloride. Extracts were cleaned up by solid-phase extraction mixed-mode column using quaternary amine and aminopropyl sorbents. The pesticides were determined by gas chromatography with electron capture detector. The recoveries from three vegetables: carrot, cucumber and green mustard, spiked at 0.25-0.5 mg/kg were 72.0 to 117.0%. The results were comparable to those obtained by the silica gel cleanup method.